FINANCIAL ACCOUNTING AND VALUATION OF INTANGIBLE ASSETS - Arrarte Mera, Raúl Alberto (2015)
Intangible assetsThis investigation was sponsored by Vice President for Research of San Marcos, in 2014. It is an exploratory documentary review which concludes that there is no clear evidence by the Accounting Standards Board (IASB) to recognize as intangible the fundamental tools used in the business management of integrated companies into the Human Factor, Customer Factor and Organizational Factor. It is of public need to expand the current Framework for the Preparation and Presentation of Financial Statements of existing international standards to non-financial information. Validating in those terms, prospective instruments like Strategic Planning, the Balanced Scorecard, Intellectual Capital and Added Economic Value; making the accounting science predictable in the long term. If a dispute is stated in the terms outlined above, it would only promote the mandatory use of management tools already mentioned; enhancing and thus normalizing, the technical level of non-financial information globally.